#### Answer

1) If x = 0, then y = 6
2)If y = -2, then x = 4
3)If x = 3, then y = 0
Table:
x | y
1) 0 | 6
x | y
2) 4|-2
x | y
3) 3 | 0

#### Work Step by Step

The equation is: 2x + y = 6
Thus, the given values should satisfy the equation.
1) In the equation, if we put x = 0, then:
2(0) + y = 6
y=6
Thus if x = 0, then y = 6.
2) In the equation, if we put y = -2, then:
2x -2 = 6
Adding 2 on both sides,
2x - 2 + 2 = 6 + 2
2x = 8
Dividing by 2 on both sides,
x = 4
Thus, if y = -2, then x = 4
3) In the equation, if we put x = 3, then:
2(3) + y = 6
6 + y = 6
Subtracting six from both sides,
6 - 6 + y = 6 - 6
y = 0
Thus, if x = 3, then y = 0.